Perancangan Aplikasi Penjualan Berbasis Web Pada Toko HUAT JAYA PLYWOOD - Calvin Wijaya; Wasino (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
This thesis proposes a web application for sales recording at Huat Jaya Plywood, aiming to optimize sales transactions and reports digitally. The system replaces paper-based records to improve operational efficiency, where staff can record orders online via laptops provided, but customers can also enter orders independently. Key features include digital recording of all transactions and inventory management, reducing paper usage, and simplifying stock management and revenue monitoring. This is important for owners to analyze sales and support data-driven business decisions.The app is designed for three types of users: owners, staff, and customers. The owner manages products and orders, the staff is in charge of recording customer orders, and customers can input orders independently as well as through laptops provided in the store. The system will include frontend and backend using HTML, CSS, PHP, and MySQL as the database. This web-based application will provide a strategic tool for the owner in managing and developing Huat Jaya Plywood's business in the plywood sales industry to be more modern and competitive.